2020
DOI: 10.1126/sciadv.abc5586
|View full text |Cite
|
Sign up to set email alerts
|

The healthy exocrine pancreas contains preproinsulin-specific CD8 T cells that attack islets in type 1 diabetes

Abstract: Preproinsulin (PPI) is presumably a crucial islet autoantigen found in patients with type 1 diabetes (T1D) but is also recognized by CD8+ T cells from healthy individuals. We quantified PPI-specific CD8+ T cells within different areas of the human pancreas from nondiabetic controls, autoantibody-positive donors, and donors with T1D to investigate their role in diabetes development. This spatial cellular quantitation revealed unusually high frequencies of autoreactive CD8+ T cells supporting the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 44 publications
1
50
1
Order By: Relevance
“…Remarkably, many CD8 T cells recognized the PPI 15-24 epitopes (15). In contrast to previous studies, where less than 1% of autoreactive CD8 T cells were detected within the peripheral blood (4, 5), frequencies in the pancreas are much higher (30-40%) (15). Besides, the majority of PPI-reactive CD8 T cells in the exocrine pancreas were positive for CD45RO, suggesting an antigen-experienced phenotype.…”
Section: The Presence Of Autoreactive Cd8 T Cells In the Target Organcontrasting
confidence: 90%
See 3 more Smart Citations
“…Remarkably, many CD8 T cells recognized the PPI 15-24 epitopes (15). In contrast to previous studies, where less than 1% of autoreactive CD8 T cells were detected within the peripheral blood (4, 5), frequencies in the pancreas are much higher (30-40%) (15). Besides, the majority of PPI-reactive CD8 T cells in the exocrine pancreas were positive for CD45RO, suggesting an antigen-experienced phenotype.…”
Section: The Presence Of Autoreactive Cd8 T Cells In the Target Organcontrasting
confidence: 90%
“…Notably, the study showed that many PPI 15-24 -specific CD8 T cells are present in the exocrine pancreas of healthy donors and donors with autoantibodies supporting the theory of a general leakiness of central tolerance. In T1D patients, these cells were not only enriched in the exocrine pancreas but were also present within the islets or close to the islets (15). The PPI-specific CD8 T cells significantly infiltrated insulincontaining islets suggesting a critical effector mechanism leading to beta-cell destruction.…”
Section: The Presence Of Autoreactive Cd8 T Cells In the Target Organmentioning
confidence: 95%
See 2 more Smart Citations
“…These T cells may reside long-term and expand in situ as has been shown for tissue resident memory T cells in skin [ 45 ], or they could be recruited to islets throughout ageing by secreted factors or the accumulation of an antigen target. In the future, it would be interesting to compare T cell populations in the islets to the exocrine pancreas during ageing, as this could be a source of islet T cells, as was recently suggested in type 1 diabetes [ 46 ]. The correlation between the progressive increase in insulin secretion during ageing, observed in this study and others [ 34 37 ], and the progressive accumulation of islet T cells reported here, is intriguing.…”
Section: Discussionmentioning
confidence: 99%